474 Incidence and Risk Factors for Perioperative Stroke Following Resection of Intracranial Tumors: A Nationwide Analysis of 30, 951 Cases. (April 2023) - Kassicieh, Alex; Varela, Samantha; Rumalla, Kavelin NA; Kazim, Syed Faraz; Bowers, Christian Andrew
Abstract : INTRODUCTION: Perioperative cerebrovascular accidents (CVA) in neurosurgical patients is a serious complication that may result in permanent neurological deficits. Establishment of associated risk factors allows for mitigation of CVA risk and sequelae. METHODS: The National Surgical Quality Improvement Program (NSQIP) database was queried for cranial tumor excision cases (2015-2019, N = 30, 951). Univariate and multivariable analysis of demographic data and comorbidities was used to assess predictive strength of these factors on postoperative CVA. RESULTS: CVA occurred in 1.7% of cases (N = 532). Patients with CVA, on average, were older, frailer, with increased rates of diabetes mellitus, hypertension, and weight loss. In multivariable analysis, predictors of CVA included advanced age (≥75th percentile in cohort)(OR: 1.9, 95% CI: 1.4-2.5), diabetes mellitus (OR: 1.4, 95% CI: 1.1-1.8), hypertension (OR: 1.4, 95% CI: 1.1-1.7), and weight loss (OR: 1.9, 95% CI: 1.1-3.2). Increased proportions of CVA were found among patients with primary malignant brain tumors (46.1%) and meningiomas (32.9%) when compared to all other benign brain tumors (6.6%) and secondary metastatic brain tumors (14.5%)(all p < .001). Elective surgery status was associated with decreased likelihood of CVA (OR: .74, 95% CI: .60-.91). In multivariable analysis, increasing frailty (as measured by mFI-5 and RAI-revised) was associated with increasing likelihood of CVA. CONCLUSIONS: The current study was the largest to identify preoperative risk factors for perioperative stroke after resection of intracranial tumors. Patients with advanced age, multiple comorbidities, and higher frailty scores were significantly more likely to suffer CVA. Frailty (as measured by mFI- and RAI-revised) is a valuable tool for preoperative risk stratification.